Exploring the Use of an Augmented Reality Device Learning Tool for Multidisciplinary Staff Training on Domestic Abuse and Sexual Violence: Postintervention Qualitative Evaluation - Dilroshini Karunaratne; Jessica Whittock; Amber Moore; Krishna Dasigan; Jasmine Chevolleau; Brent Bartholomew; Nikki Kelly; Charlotte E Cohen (JMIR Formative Research)
Abstract BackgroundLegislative policies published by National Health Service, England and the UK Government focus on prioritizing the creation of a stronger system. These frameworks emphasize on the improvement of health care staff’s ability to identify and refer domestic abuse (DA) survivors as key areas for supporting workforce development. Health care staff are often the first professional contact of survivors of DA, and insufficient staff training is a key barrier to survivors being identified and directed to support. The Microsoft HoloLens2 is a mixed-reality headset that allows virtual objects (holograms) to be integrated into the real world. Mixed-reality headsets are being increasingly used within medical education and have the advantage of independent operation, reducing the staffing requirements for teaching. The HoloLens2 can be used to project HoloPatients (HPs), which resemble clinically unwell patients, into the classroom. Two of these HPs have been specifically designed to portray survivors of DA and sexual violence (SV). ObjectiveThis study explored potential uses of the HP in DA and SV training as a potential survivor-centered educational initiative that could be used as an adjunct to existing training for health care professionals and community sector workers. MethodsFrontline staff and community stakeholders from the national health service, DA, and law enforcement sectors were invited on 3 separate occasions (n=14, 12, 22) to a HoloLens2 demonstration that displayed 9 HPs. The patient voice was to be outlined by personalized scripts, co-created alongside sector charities, ensuring survivor engagement and participation. Participants were given the opportunity to wear the headset and familiarize themselves with the technology during the sessions. A post-intervention evaluation research model was used to explore the feasibility and functionality of the HP as an educational tool. ResultsThematic analysis described the HP as a “realistic,” “adjustable” tool that “creates a safe learning environment.” Participants suggested it could be useful in “pre-exposure preparation” by “improving communication” and allowing different approaches to be trialed in a safe environment. The use of survivor scripts was described as a useful tool to “bring the survivor into the learning space” in a safe way. Participants identified the HP as a suitable tool for workers inside and outside health care, including social sectors such as law enforcement (32%). ConclusionsThe HP acts as a low-risk, adaptable tool for trainees to develop skills in a safe environment. This study demonstrates that professionals perceived the HoloLens as an innovative means to amplify the lived experience voice. Further research will evaluate this additional impact on trainees’ confidence and responses to survivors disclosing DA and SV within different disciplines to drive improved outcomes.